Knowing the Abuser Inside and Out: The Development and Psychometric Evaluation of the Identification With the Aggressor Scale - Lahav, Yael (Journal of interpersonal violence, 2021)
Identifying with the aggressor is a process wherein victims of abuse, particularly during childhood, take on their perpetrator’s experience. The victim defers to the perpetrator and adopts the perpetrator’s experience, learns the perpetrator’s desires and needs, and gratifies them. Although the clinical and theoretical literature suggests that identification with the aggressor occurs in the aftermath of abuse and has negative long-term implications, to date this concept has not been empirically investigated. To facilitate an exploration of this subject, the current study evaluated the psychometric properties of a new measure: the Identification With the Aggressor Scale (IAS). The study was conducted among convenience samples of students using online surveys. In Study 1, the IAS was administered to 318 students. In Study 2, the IAS, and a battery of questionnaires assessing features of abuse, dissociation, posttraumatic stress disorder (PTSD) symptoms, and posttraumatic guilt were administered to a convenience sample of 368 students. Four reliable IAS factors emerged from Study 1: Adopting the perpetrator’s experience concerning the abuse, identifying with the perpetrator’s aggression, replacing one’s agency with that of the perpetrator, and becoming hypersensitive to the perpetrator. In Study 2, a confirmatory factor analysis confirmed the scale’s underlying factor structure. A history of childhood abuse, recurrence and severity of abuse, and the perpetrator being a parental figure were all associated with higher IAS scores. In addition, IAS scores were correlated with dissociation, PTSD symptoms, and posttraumatic guilt. The present findings indicate that the IAS has good psychometric properties, making it useful as an assessment tool in future research.